Factors Affecting GRDP and Efficiency Level of Food Crops Sub-sector in East Java - Hermansyah, Dhany; Hanani, Nuhfil; Muhaimin, Abdul Wahib (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
The strategic roles of agriculture are provider of food and raw material for the industry, as well as contributor of Gross Regional Domestic Product (GRDP), foreign exchange earnings, and the main employer. Based on the total GRDP of agriculture, food crops have the highest value compared to other subsectors. However, when compared to other sectors, the the total GRDP of the agricultural sector inin East Java is still lower than that of the manufacturing and trade sectors. To increase its contribution, Â agricultural sector needs policies, regulations, programs and specific intervention for food crops performance in each district. The objectives of the study were to analyze factors affecting the GRDP of food crops sub-sector in East Java, and to analyze the efficiency level of the food crop sub-sector in the districts/cities in East Java. The research method was the Stochastic Frontier Analysis with Front 4.1 application. The dependent variable was GRDP of Â food crops, and the independent variables consist of irrigated land, dry land area, the number of agricultural labors, the number of subsidized fertilizer, the subsidized of two-wheel tractors, and water pump. Based on the survey, the factors that significantly influence the GDP were irrigated land area, dry land area, number of employees, and subsidized two-wheeled tractors. The findings suggested that the area of irrigated land, dry land, the number of labor, and the subsidized two-wheel tractor had significant effect towards the GRDP of the food crops sub-sector. However, the amount of subsidized fertilizer and water pump assistance did not significantly affect the GRDP of the food crops sub-sector. The average efficiency level of the food crops sub-sector in East Java was 0.77 with a minimum efficiency of 0.44 in Mojokerto City and the maximum efficiency in Gresik wasÂ 0.96. The central regions of the food crop sub-sector had an average of high efficiency, while the low-efficiency regions were the urban areas.